Pharmacists' stigma toward patients engaged in opioid misuse: When "social distance" does not mean disease prevention. Issue 4 (2nd October 2021) - Werremeyer, Amy; Mosher, Sydney; Eukel, Heidi; Skoy, Elizabeth; Steig, Jayme; Frenzel, Oliver; Strand, Mark A.
Abstract: Background: Health professionals may stigmatize and prefer social distance from patients with opioid misuse, leading to poorer quality of care provided. The degree to which pharmacists prefer social distance from patients with opioid misuse and opioid use disorder (OUD) is not known. Methods : Pharmacists ( n  = 187) completed a survey comprised of demographics, attitudinal, and Social Distance Scale (SDS) questions based on a vignette patient who displayed opioid misuse. SDS question responses and total scores (maximum of 30; higher scores representing great preference for social distance) were tallied and associations with attitudes and demographics were examined. Results : Mean SDS total score was 16.32 (range 9–23). More than 59% of respondents had an SDS score >15, indicating overall lack of willingness to interact with the vignette patient. Females had a higher mean SDS score vs male pharmacists (16.58 vs. 15.36, respectively; p  = 0.023). Pharmacists were more likely to prefer social distance from the vignette patient in personal situations (i.e. renting a room) than work-related interactions (i.e. providing patient education). Pharmacists with >10 years of experience, those without personal experience with a substance use disorder, those who strongly agreed that patients with OUD require excessive time and effort, and those who agreed that some people lack self-discipline to use prescription pain medication without becoming addicted had significantly higher SDS scores than pharmacists without these characteristics. Conclusions : Pharmacists expressed significant preference for social distance indicating stigmatization of patients with opioid misuse. Pharmacists were comfortable performing pharmacy tasks with patients with opioid misuse, but were less comfortable forming therapeutic relationships, an important tenet of patient-centered care. Efforts are needed to examine contributions to social distance preferences and implement measures to reduce them. Targeting of pharmacists with >10 years' experience and without personal experience with OUD may also be most beneficial.